Dluga droga do domu - Steel, Danielle (Katowice : Wydawn. "Ksiaznica", 1998)
A translation of "Long Road", a novel about the abuse of a young girl who becomes a famous author.
Translation of: The long road.
Keywords: Child abuse -- Fiction; Women authors -- Fiction; New York (N.Y.) -- Fiction